Effects of Variable Humidity on the Creep Behavior of Concrete and the Long-Term Deflection of RC Beams - Pengfei Li; Shiqin He (Advances in Civil Engineering)
The influences of variable humidity on the creep behaviors of concrete and the long-term deflections of RC beams are analyzed in this paper. A total of 6 prismatic specimens and 5 RC beams were subjected to sustained loads and 3 types of variable humidity conditions for 331 days. The creep strains of the prismatic specimens and the deflections of the RC beams were recorded to investigate the long-term deformation characteristics. The test results reveal that both the creep strain and the deflection of specimens under cyclic humidity conditions exhibit approximately linear tendencies that are obviously less than those of specimens exposed only to natural air. During certain wetting cycles, the deformation rate became slower and the creep strain even recovered with an increase in the humidity, especially for shorter wetting-drying cycles. Long-term deflections predicted using the CEB-FIP 90 and ACI 209R models were compared with the test results to evaluate the versatility of these current specifications. The findings included rather large errors between the predicted results and experimental data when the average relative humidity was adopted in the analytical models.